Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo - Ng, Heok Hee; Hadiaty, Renny K. (Zootaxa, 2019)
A new species of bagrid catfish in the genus Leiocassis is described from the Mahakam River drainage in eastern Borneo. Leiocassis rudicula, new species, can be distinguished from congeners in having a unique combination of: distinct concavity at level of orbit in dorsolateral profile of head; tip of supraoccipital spine not reaching anterior nuchal plate element; smooth posterior margin of dorsal spine; presence of an irregular pale band on sides of body between dorsal and adipose fins; anal fin with narrow brown band across middle third of fin; narrow caudal-fin lobes with nearly straight posterior margins; snout length 36–40% HL; eye diameter 14–20% HL; head depth 17.6–20.0% SL; length of dorsal-fin spine 14.1–18.5% SL; length of pectoral-fin spine 15.1–17.7 %SL; dorsal-to-adipose distance 10.9–14.3% SL; body depth at anus 16.4–19.5% SL; length of adipose-fin base 18.9–24.1% SL; length of anal-fin base 18.8–22.6% SL; and caudal peduncle depth 9.1–10.9% SL. A revised key to the genus is also provided.